THE INCREASE IN CHILDREN'S INDEPENDENCE THROUGH OUT BOUND ACTIVITIES FOR 4-5 YEARS - Hidayatun Naimah; Purwati Purwati; Reza Edwin Sulistryaningtyas (Prosiding University Research Colloquium, 2022)
This study aims to determine the increase in children's independence throughOut Bound activities for 4-5 years group A in BA. Al-Kautsar TIDAR Islamic BoardingSchool in Magelang City using the CAR (Classroom Action Research) method. This typeuses 2 cycles with stages including planning, implementation, observation and reflectionstages. The research subjects were students of group A in BA. Al-Kautsar, totaling 12children consisting of 5 girls and 7 boys. The data collection method uses non-test in theform of observation. Based on the results of the research and discussion, it can beconcluded that the increased independence skills of child A in BA. Al-Kautsar can beimproved through circuit games. The increase that occurs can be seen from the researchstage, namely observations made during pre-action, implementation of actions in cycle Iand cycle II. his is indicated by the results achieved by the subject from the initialconditions or before the increased independence ability action was carried out in the lowcategory. Group A in BA. Al-Kautsar experienced an increase in increased independenceskills from pre-cycle by 441,1% , increased in cycle I to 65,9% and increased to 87,2% incycle II. From these results it can be seen that the increased independence skills ofchildren have reached the success criteria expected by researchers.